Case report: Thrombotic thrombocytopenic purpura in a pregnant woman with lupus membranous nephropathy: a diagnostic challenge - Leiva, Marina; Navarro, Gustavo; Carpio, J Daniel; Ardiles, Leopoldo (Frontiers in Nephrology, 2024)
A 27-year-old female at 20th week of pregnancy was admited with edema, foamy urine, but normal blood pressure. Her blood count was normal, she had proteinuria of 3 g/day, creanine 0.4 mg/dl, albumin 2.4 g/dl, and cholesterol 355 mg/dl. Annuclear anbodies 1/160, but An-DNA, ancardiolipin anbodies and lupus ancoagulant were negave, with normal serum C3 and C4. A renal biopsy showed secondary membranous glomerulopathy, most likely lupus class V pure.Steroids, azathioprine, and aspirin were iniated, up to 28 weeks of pregnancy, when she developed severe hypertension, photopsia, headache, anasarca, extensive bruising of the extremies, severe anemia, thrombocytopenia, and creanine rose to 2.09 mg/dl with preserved diuresis. A female infant, 1045 grams, was delivered by emergency caesarean secon. Following the surgery, she experienced diplopia, dysarthria, bradypsychia, and sensory alteraons in the lower extremies, necessitang emergency hemodialysis due to pulmonary congeson. Blood smear revealed schistocytes, LDH elevated at 1148 IU/L, while transaminases and liver funcon remained normal, suggesng thromboc thrombocytopenic purpura. ADAMTS13 revealed 6% acvity with the presence of inhibitor. Mycophenolate and daily plasmapheresis with fresh frozen plasma replacement yielded unsasfactory response, unaffected by the addion of methylprednisolone pulses and rituximab. Eventually, intravenous cyclophosphamide was introduced, resulng in complete hematological remission and normalizaon of ADAMTS13, however dialysis-dependence persisted and four years later, right renal cancer prompted bilateral nephrectomy. Aer a total follow-up of six years, she remained free of neoplasc recurrence and lupus acvity, receiving prednisone and hydroxychloroquine. The differenal diagnosis of microangiopathic syndrome in a pregnant lupus paent is discussed.